(3cJGH GdNjhd hGdaQhSjIs - (3eLghds; (3CHh YHO Gddg fGUQ GdOjf , GHf GNj MRGe GdNWdj, CHh YHO Gddg fGUQ GdOjf , GHf GNj MRGe GdNWd,J (B250 (3g` s
(3ChdgG (B:s
(3CeGHYO de CRd HYO hgH Gddg di ef GdeYQag HGdBOGH HGdaQhSjI eG hgH s
(3cJHJ HQSe NRGfI GdLfGH GdYGdi GdCejQi eMeO CejQ MhQ GdfGUQi hHgG HYV UhQ ddNjhds
(3hHBNQ hQbI (B32: (3Je GdcJGH GdHjWQIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B145s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs